EVALUATION OF SOLD DRINKING WATER IN IBB CITY IN THE PERIOD BETWEEN (2019-2023) (Journal of Libya for geographical studies, 2024)
This research aims to extract the numerical and relative variation in the values of the amount of water sold and lost, as well as the analysis and interpretation of the numerical data of the records of monitoring the amount of water sold and lost in the city of Ibb during the period between (2023-2019), and the research concluded a number of results, the most important of which are: The continuous increase in the values of the quantities of water sold annually in the city of Ibb, as the largest value in the amount of water sold in the year (2023), (5,101,362 m3/year), and an increase rate of (138.3%), while the highest was recorded A value of the average daily per capita amount of water sold in the year (2022), (26 liters per day/person), with an increase rate of (124%), and the highest percentage of increase in the amount of water losses was monitored in the city of Ibb in the year (2023), reaching (250%), as a result of the increase in the volume of water losses during the period between (2019-2023) from approximately (806,563 m3/year) in (2019) to (2,018,779 m3/year) (2023), and this study showed that the general average per capita share of water Sold about (24 liters / day), which indicates an increase in water losses during the water distribution phase to subscribers, which means that there are malfunctions or fractures in the drinking water distribution network for subscribers, as it was noted that the general rate of water losses (NRW) increased during the period between (2019-2023) to (23%) of the annual water production volume for the period (2019-2023), and the general rate of water loss (UFW) increased to (30.2%) of the volume of water sold during the period between (2019-2023), and it is possible Achieving a reduction in water losses in Ibb city to (25%) in the long term within (5) years on average, which is acceptable from a financial and investment point of view.
Keywords: Water Sold; Average Per Capita Value; Assessment of Drinking Water Loss, Reduction of Water Loss; Ibb City - Yemen